INTEGRASI PERMAINAN TRADISIONAL DALAM PENINGKATAN KETERAMPILAN MOTORIK KASAR SISWA SEKOLAH DASAR - Shodiq, Moh. Nur; Priambodo, Anung; Pudjijuniarto; Nurlaila (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the effectiveness of integrating traditional games in improving the gross motor skills of elementary school students. The research method used is experimental with a pre-test and post-test one group design. The population consisted of fourth-grade students from an elementary school, with a sample of 30 students selected from one class. The instrument used to measure gross motor skills was the Test of Gross Motor Development-2, which has been adapted and validated for the Indonesian context. Data analysis showed a significant increase in gross motor skills after participating in traditional game interventions. The pre-test data were not normally distributed (Sig. Shapiro-Wilk = 0.007), while the post-test data were normally distributed (Sig. = 0.128). The paired t-test results indicated a t-value of 132.366 with a p-value of 0.000 < 0.05, confirming a significant improvement. The traditional games specifically used in this study were Boi-boian and kasti. Boi-boian involves actions such as throwing and dodging, which effectively develop coordination and reaction skills. Kasti, a bat-and-run game, trains students in hitting, catching, and sprinting, enhancing strength, agility, and motor accuracy. The integration of these two games provided diverse physical challenges and significantly boosted student engagement.These findings suggest that traditional game-based interventions can serve as an effective strategy for enhancing gross motor skills in elementary school students.